Utilizing WhatsApp Groups for Family Communication and Interaction: Memanfaatkan Grup WhatsApp untuk Komunikasi dan Interaksi Keluarga - Sabilla, Talitha Rizda; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2025)
Family communication is an important element in building harmonious relationships between family members. In the digital era, technology makes daily communication and interaction easier. This study aims to understand family communication in the digital era in Sidoarjo Regency, through interviews with five respondents from various backgrounds. The results of the study show that digital technology makes it easier for families to stay connected despite being apart. Respondents revealed great benefits in maintaining family relationships through text messages, video calls, and social media, as well as sharing life moments in real-time. Nonetheless, challenges such as technical issues and privacy concerns remain. It is important for families to maintain a balance between digital and face-to-face interactions to ensure that the quality of the relationship is maintained. Technology provides convenience, but direct interaction is still important in building strong emotional bonds. Highlights: Digital technology facilitates family communication despite physical distance. Benefits include real-time sharing and maintaining relationships through text, video, and social media. Balancing digital and face-to-face interaction is essential for strong emotional bonds. Keywords: Communication, Family, Whatsapp